Covid-19, economy and the ‘drop of honey effect’ metaphor – a note on the Portuguese case. Situation and measures - Filipe, J. (International Journal of Business and Systems Research, 2021)
Covid-19 appeared in Wuhan (China), by December, 2019 and rapidly spread to the rest of the world. Many countries adopted measures against its spread to protect people and national health care services. However, at the moment more than 2.5 million people got infected and more than 175 thousand died in the 213 countries, areas and territories reached by the disease (official records at April 23, 2020). Countries began to adopt also measures to protect the economy and to prepare the economic recovery, once the effects are tremendous worldwide. In Portugal, measures allowed a flattered curve for Covid-19 spread. In this paper we use an analogy to the “drop of honey effect” to show how this curve develops. The “drop of honey effect” is studied in terms of chaos theory and dynamic systems and is used as a framework to the way systems change in social phenomena.